Research on the Impact of Education Involution on County-level Education Development - Wu, Xiaoyue (Journal of Educational Research and Policies, 2025)
Education involution is an unhealthy competition in education caused by the differentiation of high-quality educational resources. This research finds that the main reasons for the internal competition in county-level education lie in the limited high-quality educational resources in counties, parents’ high educational expectations, and the single evaluation mechanism of the college entrance examination. The involution in education has increased family education anxiety and intensified unhealthy competition; has increased the educational expectations for teachers, leading to teacher pressure; has disrupted the educational atmosphere in the county and affected social equity in the county. In response to the education involution in county-level education, proposed countermeasures including changing the concept of family education, providing educational resources with digital technology, and supporting fair school operation with policies.